Right lung agenesis in a one‐year‐old Chihuahua. Issue 3 (26th August 2020) - Martinez, Carlos; Rowan, Conor
SUMMARY: A one‐year‐old neutered male Chihuahua was referred for further investigations of spontaneous pneumothorax. Before referral, thoracocentesis and chest drain placement was performed. On presentation, the dog was dull and dyspnoeic displaying a restrictive respiratory pattern. Thoracic radiography and CT findings performed at the referral centre were consistent with right lung agenesis and pneumothorax. Retrospective review of the radiographs obtained at the referring practice identified right‐sided mediastinal shift, separation of the cardiac silhouette from the sternum and overinflated left lung lobes. Neither free intrathoracic gas nor subcutaneous emphysema was identified. The initial images were suboptimally displayed resulting in artefactual 'blackening' of the lung parenchyma, necessitating digital manipulation to identify lung markings. The combination of mediastinal shift and separation of the cardiac silhouette from the sternum as a result of the right lung agenesis could potentially lead to a false impression of pneumothorax.